Effect of Feed Form and Duration Time in Growing Period on Broilers Performance - Agah, M.J.; Norollahi, H. (International Journal of Poultry Science, 2008)
In a completely randomized design, (with 6 treatments and 3 replications) the effect of feeding mash, pellet and crumble diets and duration time on performance of broilers was studied. 936 Ross broilers randomly allocated to one of following treatments: T1) mash diet in total growing period (TGP) (control diet), T2) pellet diet in TGP, T3) pellet diet in starter and mash diet in other growing period (OGP), T4) mash diet in starter and pellet diet in OGP, T5) crumble diet in first ten days and mash diet in OGP, T6) mash diet in first ten days and pellet diet in OGP. All of chickens were fed with iso energetic and iso nitrogenous diets, for six weeks. In total period (1 to 42 days) feed intake was minimize for T2. Treatments had not different significant effects on weight gain and feed conversion ratio (FCR), but Duncan test were showed a significant difference between T3 and T6 (1859g vs. 2090g and 1.99 vs. 1.73 respectively). The lowest FCR and the highest weight gain were belonged to T6. Carcass, abdominal fat and heart weight percentages to live weight did not significantly differ.